Negative electrode material with high energy storage and application of negative electrode material in solid-state battery

Through the preparation of carbon-coated SiO2/C composite materials, combined with the generation of SiOx/C and conductive polymers, the problems of insufficient energy storage and conductivity of the negative electrode materials of solid-state battery are solved, and efficient and low-cost negative electrode materials are achieved, improving the preparation of high-efficiency and low-cost negative electrode materials. The energy density and cycle stability of the battery are achieved.

CN119252876APending Publication Date: 2025-01-03湖州启源金灿新能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411207553.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The negative electrode materials of existing solid-state batteries have problems such as insufficient energy storage performance, poor conductivity, complex and expensive preparation process, which limits their promotion in practical applications.

Method used

The preparation process of carbon-coated SiO2/C composite material is adopted to form the SiOx/C composite material through the treatment of electronic grade hydrochloric acid, SiCl4, ethyl orthosilicate (TEOS) and ammonia water, and the conductive polymerization is formed by the reaction of HCl and aniline. enhances the electrochemical properties and energy density of materials.

Benefits of technology

The preparation of negative electrode materials with high energy storage and high conductivity is achieved, which significantly improves the energy density and cycle stability of the battery and reduces the preparation cost and complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252876A_ABST
    Figure CN119252876A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode material with high energy storage and application of the negative electrode material in a solid-state battery, which comprises the following steps: preparation of electronic grade hydrochloric acid, preparation of SiCl4 (silicon tetrachloride), preparation of tetraethoxysilane (TEOS), preparation of carbon-coated SiO2 / C, preparation of a SiOx / C composite material, preparation of Si / SiOx / C and the like. The preparation method creatively combines a high-temperature oxidation process, a liquid-solid contact process, a dehydration stabilization process and other preparation methods. The carbon-coated SiO2 / C is adopted, so that the prepared Si / SiOx / C negative electrode material has good conductivity, the carbon-coated SiO2 / C layer is used as an elastic buffer layer to absorb and relieve stress caused by silicon volume change, and the structural integrity of the negative electrode material and the continuity of a conductive network are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode material with high energy storage and application of the negative electrode material in a solid-state battery. Background Art

[0002] With the surge in global energy demand and the awakening of environmental awareness, the development of efficient and environmentally friendly energy storage solutions has become a top priority. The massive consumption of traditional fossil fuels has not only exacerbated the greenhouse effect, but also led to an increasingly serious energy crisis. Against this background, new energy technologies, especially high-efficiency and long-life energy storage devices such as solid-state batteries, have become a research hotspot. Solid-state batteries are regarded as an important part of future energy storage systems due to their excellent safety performance, high energy density, and good cycle stability.

[0003] In the core components of solid-state batteries - negative electrode materials, researchers are committed to finding new materials that are both environmentally friendly and efficient to overcome the limitations of existing technologies, such as electrolyte leakage and flammability, which are common in lithium-ion batteries. Ideal negative electrode materials should have high energy storage capacity, good conductivity and minimized impact on the environment. However, many negative electrode materials on the market currently either have insufficient energy storage performance or poor conductivity, or the preparation process is complicated and costly, which limits their promotion in practical applications. Therefore, it is particularly important to develop a negative electrode material with a simple preparation process, controllable costs, high energy storage and high conductivity. By overcoming this technical difficulty, we can hope to achieve a cleaner and more sustainable energy future. Summary of the invention

[0004] In view of the above problems, the present invention provides a negative electrode material with high energy storage and its application in solid-state batteries.

[0005] The first technical purpose of the present invention is to prepare carbon-coated materials.

[0006] The second technical purpose of the present invention is to prepare negative electrode materials.

[0007] The present invention relates to a negative electrode material with high energy storage and its application in a solid-state battery, comprising the following steps: preparation of electronic grade hydrochloric acid, preparation of SiCl4 (silicon tetrachloride), preparation of tetraethyl orthosilicate (TEOS), preparation of carbon-coated SiO2 / C, preparation of SiO x Preparation of / C composite materials, preparation of Si / SiOx / C.

[0008] Preferably, step (1) preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a certain ratio to generate a by-product of hydrogen chloride (HCl). The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber. The top temperature of the washing tower is controlled below zero. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic grade hydrochloric acid is obtained; Step (2) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions and the product is chlorinated at high temperature to obtain SiCl4 (silicon tetrachloride); Step (3) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor in a certain mass ratio, react together, raise the temperature together, and react for a period of time to obtain tetraethyl orthosilicate (TEOS); Step (4) Preparation of carbon-coated SiO2 / C According to a certain ratio, ethanol, deionized water and tetraethyl orthosilicate (TEOS) in step (3) are sequentially placed in a beaker, stirred, and after sufficient stirring, a mixed solution is obtained, the mixed solution is poured into a citric acid solution, and then ethylene glycol is dripped into the citric acid solution according to a certain volume ratio, stirred at a constant temperature, dried in an electric oven, and the solid is taken out and ground into powder, and then pre-fired in a tubular furnace. After the pre-fired treatment is completed, xenon gas is introduced into a tubular furnace for calcination to obtain carbon-coated SiO2 / C; Step (5) Preparation of SiOx / C composite material A small amount of the carbon-coated SiO2 / C prepared in step (4) is added to deionized water, stirred, and ammonia (NH3H2O) is added and stirred continuously. The solution is heated and reacted for a period of time. The silicon submicron sphere precursor is collected by centrifugation. The silicon submicron sphere precursor is then placed in a corundum crucible and placed in a tube furnace. The temperature is raised at a certain rate and calcined in an Ar (argon) atmosphere. After cooling, SiO2 / C is obtained. x / C composite materials; Step (6) Preparation of Si / SiOx / C Take a small amount of SiO xThe Si / SiOx / C composite material is added into HCl (hydrogen chloride) to form a solution, ultrasonicated at room temperature for a period of time, added with a small amount of aniline (C6H7N), transferred to a magnetic stirring at room temperature, ammonium persulfate is weighed, an ammonium persulfate solution is prepared, and then magnetic stirring at room temperature is continued to obtain a dark green suspension, which is centrifuged, vacuum dried, and placed in a tubular furnace for carbonization under an Ar (argon) atmosphere for a period of time to obtain Si / SiOx / C.

[0009] The first technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (1) preparation of electronic grade hydrochloric acid With trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 1-5:2-7 to generate a by-product of hydrogen chloride (HCl). The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber with an operating pressure range of 0-60 kPa and an operating temperature range of -25-80°C. The top temperature of the washing tower is controlled at -35--25°C, the pressure is controlled at 0.9-1.1 MPa, and the temperature difference is controlled at 0-5°C. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower, and after screening, electronic grade hydrochloric acid is obtained.

[0010] The advantage of adopting the present invention is that, in the washing tower of this step, hydrogen chloride (HCl) is fully absorbed by contacting with low-concentration hydrochloric acid, thereby reducing other impurities, making the hydrogen chloride obtained at the top of the tower higher in purity, obtaining better electronic-grade hydrochloric acid, and laying a solid foundation for the next step of preparation.

[0011] Preferably, step (2) preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove the alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions and the product is chlorinated at high temperature (600-1100°C) to obtain SiCl4 (silicon tetrachloride).

[0012] The advantage of adopting the present invention is that in this step, the carbonization efficiency of rice husk under anaerobic conditions is high, and when it is converted into inorganic carbon, the gas released can help reduce the oxygen in the reaction system and reduce the formation of oxides.

[0013] Preferably, step (3) preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor in a mass ratio of 1-5:1-5 g, react together at 10-15° C., heat to 30-40° C., and react for 2-5 hours to obtain tetraethyl orthosilicate (TEOS).

[0014] The advantage of the present invention is that in this step, anhydrous C2H5OH (anhydrous ethanol) is used as the reactant and the solvent, which ensures sufficient contact between the reactants, is beneficial to improving the purity of the product, and makes the hydroxyl group (-OH) in the ethanol react with SiCl4, so that SiCl4 and the hydroxyl group in the ethanol undergo a substitution reaction to obtain tetraethyl orthosilicate (TEOS).

[0015] Preferably, step (4) preparation of carbon-coated SiO2 / C In a beaker, ethanol, deionized water and tetraethyl orthosilicate (TEOS) in step (3) are placed in a ratio of 13-20:1-5:2-10 by volume, and stirred for 1-5 hours. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 0.3-0.9 g / mL citric acid solution. Then, ethylene glycol is dripped into the citric acid solution in a ratio of 1-5:40-80 by volume, and stirred at a constant temperature of 60-100 °C. 0℃, dried in an electric oven, the drying temperature and time are 120-150℃ and 12-20h respectively, take out the solid and grind it into powder, and pre-sinter it in a tubular furnace. The pre-sintering atmosphere, temperature and time are air atmosphere and 350-600℃ and 4-10h respectively. After the pre-sintering, xenon gas is introduced into the tubular furnace for calcination, the calcination temperature and time are 900-1000℃ and 4-10h respectively, to obtain carbon-coated SiO2 / C.

[0016] The advantage of the present invention is that, in this step, ethanol and deionized water are used as media to promote the hydrolysis of tetraethyl orthosilicate (TEOS) to form SiO2 sol, and tetraethyl orthosilicate (TEOS) is converted into Si(OH)4 in an aqueous environment and condensed to construct a SiO2 network, and then citric acid is added as a stabilizer to avoid excessive aggregation of molecules, ensure that the prepared particles are uniformly distributed in size, and lay a foundation for subsequent processing.

[0017] The second technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (5) preparation of SiOx / C composite material Take 5-10 g of carbon-coated SiO2 / C from step (4) and add it to 50-100 mL of deionized water and stir for 2-5 h. Add 5-10 mL of ammonia (NH3H2O) and continue stirring for 1-5 h. Heat the solution to 50-100 °C and react for 12-20 h. Collect the silicon submicron sphere precursor by centrifugation. Then put 5-10 g of the silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace. In an Ar (argon) atmosphere, heat it at 5-10 °C·min -1 The temperature was raised to 800-1000℃ at a rate of ℃·min-1 and calcined for 3-10h. SiO x / C composite material.

[0018] The invention has the advantage that, in this step, the introduction of ammonia water (NH3H2O) is combined with high-temperature calcination under argon protection, so that the microstructure of the SiOx / C composite material is optimized, the ammonia water (NH3H2O) adjusts the pH value, promotes the effective dissolution of SiO2, obtains more uniform SiOx, and also improves the surface properties of the composite material, and in an inert environment created by Ar (argon gas), the high-temperature calcination at 800-1000°C makes SiO2 become highly crystalline, forming a dense and uniform carbon coating structure.

[0019] Preferably, step (6) preparation of Si / SiOx / C Take 10-20 g of SiO x The Si / SiOx / C composite material was added to 1~5 mol / L HCl (hydrogen chloride) to prepare a 1~5 M solution, and ultrasonicated at room temperature for 30~60 min. 5~10 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 10~20 min. 5~10 g of ammonium persulfate was weighed to prepare a 0.5~1 M ammonium persulfate solution. The solution was then magnetically stirred at room temperature for 12~20 h to obtain a dark green suspension. The suspension was centrifuged at 9600~10000 rpm, vacuum dried at 80~100°C for 12~20 h, and carbonized at 1000~2000°C for 2~5 h in a tubular furnace under an Ar (argon) atmosphere to obtain Si / SiOx / C.

[0020] The present invention has the advantage that, in this step, SiO x The chemical reaction between the SiOx / C composite material and HCl causes the SiOx / C composite material to release silicon (Si) particles, which improves the electrochemical properties of the material, greatly enhancing the energy density and cycle stability. In addition, aniline is polymerized under the catalysis of ammonium persulfate to form polyaniline (PANI), a conductive polymer that greatly improves the electrical conductivity of the composite material.

[0021] In summary, the present invention has the following beneficial effects: The advantage of adopting the present invention is that, in the washing tower of this step, hydrogen chloride (HCl) is fully absorbed by contacting with low-concentration hydrochloric acid, thereby reducing other impurities, making the hydrogen chloride obtained at the top of the tower higher in purity, obtaining better electronic-grade hydrochloric acid, and laying a solid foundation for the next step of preparation.

[0022] The advantage of adopting the present invention is that in this step, the carbonization efficiency of rice husk under anaerobic conditions is high, and when it is converted into inorganic carbon, the gas released can help reduce the oxygen in the reaction system and reduce the formation of oxides.

[0023] The advantage of the present invention is that in this step, anhydrous C2H5OH (anhydrous ethanol) is used as the reactant and the solvent, which ensures sufficient contact between the reactants, is beneficial to improving the purity of the product, and makes the hydroxyl group (-OH) in the ethanol react with SiCl4, so that SiCl4 and the hydroxyl group in the ethanol undergo a substitution reaction to obtain tetraethyl orthosilicate (TEOS).

[0024] The advantage of the present invention is that, in this step, ethanol and deionized water are used as media to promote the hydrolysis of tetraethyl orthosilicate (TEOS) to form SiO2 sol, and tetraethyl orthosilicate (TEOS) is converted into Si(OH)4 in an aqueous environment and condensed to construct a SiO2 network, and then citric acid is added as a stabilizer to avoid excessive aggregation of molecules, ensure that the prepared particles are uniformly distributed in size, and lay a foundation for subsequent processing.

[0025] The invention has the advantage that, in this step, the introduction of ammonia water (NH3H2O) is combined with high-temperature calcination under argon protection, so that the microstructure of the SiOx / C composite material is optimized, the ammonia water (NH3H2O) adjusts the pH value, promotes the effective dissolution of SiO2, obtains more uniform SiOx, and also improves the surface properties of the composite material, and in an inert environment created by Ar (argon gas), the high-temperature calcination at 800-1000°C makes SiO2 become highly crystalline, forming a dense and uniform carbon coating structure.

[0026] The present invention has the advantage that, in this step, SiO x The chemical reaction between the SiOx / C composite material and HCl causes the SiOx / C composite material to release silicon (Si) particles, which improves the electrochemical properties of the material, greatly enhancing the energy density and cycle stability. In addition, aniline is polymerized under the catalysis of ammonium persulfate to form polyaniline (PANI), a conductive polymer that greatly improves the electrical conductivity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a flow chart of a negative electrode material with high energy storage and its application in a solid-state battery of the present invention; Figure 2 is a scanning electron microscope image of the Si / SiOx / C negative electrode material prepared in the embodiment of the present invention and the comparative example; Figure 3 1 is a charge and discharge curve diagram of Si / SiOx / C negative electrode materials prepared in the embodiments of the present invention and the comparative examples; Figure 4 It is a cycle performance diagram of Si / SiOx / C negative electrode materials prepared in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION

[0028] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0029] If not otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.

[0030] Example 1 Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 1:2 to generate a by-product of hydrogen chloride (HCl). The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber with an operating pressure range of 1kPa and an operating temperature range of -25°C. The top temperature of the washing tower is controlled at -35°C, the pressure is controlled at 0.9MPa, and the temperature difference is controlled at 0°C. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower, and after screening, electronic grade hydrochloric acid is obtained; Step (2) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions, and the product is chlorinated at high temperature (600°C) to obtain SiCl4 (silicon tetrachloride); Step (3) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor at a mass ratio of 1:1g, react together at 10°C, heat to 30°C, and react for 2h to obtain tetraethyl orthosilicate (TEOS); Step (4) Preparation of carbon-coated SiO2 / C According to the volume ratio of 13:1:2, ethanol, deionized water and tetraethyl orthosilicate (TEOS) of step (3) are placed in a beaker in turn, and stirred for 1 hour. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 0.3 g / mL citric acid solution. Then, ethylene glycol is dropped into the citric acid solution according to a volume ratio of 1:40, and stirred at a constant temperature of 60°C. The mixture is dried in an electric oven at a drying temperature and time of 120°C and 12 hours, respectively. After the solid is taken out and ground into powder, it is pre-calcined in a tubular furnace. The pre-calcination atmosphere, temperature and time are air atmosphere and 350°C and 4 hours, respectively. After the pre-calcination is completed, xenon gas is introduced into the tubular furnace for calcination at a calcination temperature and time of 900°C and 4 hours, respectively, to obtain carbon-coated SiO2 / C; Step (5) Preparation of SiOx / C composite material Take 5g of carbon-coated SiO2 / C from step (4) and add it to 50mL of deionized water, and stir for 2h, add 5mL of ammonia water (NH3H2O) and continue stirring for 1h, heat the solution to 50℃ and react for 12h, collect the silicon submicron sphere precursor by centrifugation, and then put 5g of the silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace, and heat it to 800℃ at a rate of 5℃·min-1 in an Ar (argon) atmosphere and calcine it for 3h, and then cool it down to obtain SiO x / C composite materials; Step (6) Preparation of Si / SiOx / C Take 10 g of SiO x The Si / SiOx / C composite material was added to 1 mol / L HCl (hydrogen chloride) to prepare a 1 M solution, and ultrasonicated at room temperature for 30 min. 5 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 10 min. 5 g of ammonium persulfate was weighed to prepare a 0.5 M ammonium persulfate solution. The solution was then magnetically stirred at room temperature for 12 h to obtain a dark green suspension, which was centrifuged at 9600 rpm, vacuum dried at 80 °C for 12 h, and carbonized at 1000 °C for 2 h in a tubular furnace under an Ar (argon) atmosphere to obtain Si / SiOx / C.

[0031] Example 2 Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 2:3 to generate a by-product of hydrogen chloride (HCl). The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber with an operating pressure range of 10Pa and an operating temperature range of -10°C. The top temperature of the washing tower is controlled at -30°C, the pressure is controlled at 1MPa, and the temperature difference is controlled at 2°C. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower, and after screening, electronic grade hydrochloric acid is obtained; Step (2) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions, and the product is chlorinated at high temperature (700°C) to obtain SiCl4 (silicon tetrachloride); Step (3) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor at a mass ratio of 2:2g, react together at 12°C, heat to 33°C, and react for 2.5h to obtain tetraethyl orthosilicate (TEOS); Step (4) Preparation of carbon-coated SiO2 / C According to the volume ratio of 15:2:5, ethanol, deionized water and tetraethyl orthosilicate (TEOS) of step (3) are placed in a beaker in turn, and stirred for 1.5 hours. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 0.5 g / mL citric acid solution. Then, ethylene glycol is dropped into the citric acid solution according to a volume ratio of 2:50, and stirred at a constant temperature of 70°C. The mixture is dried in an electric oven at a drying temperature and time of 13°C and 13 hours, respectively. After the solid is taken out and ground into powder, it is pre-calcined in a tubular furnace. The pre-calcination atmosphere, temperature and time are air atmosphere, 400°C and 5.5 hours, respectively. After the pre-calcination is completed, xenon gas is introduced into the tubular furnace for calcination at a calcination temperature and time of 910°C and 6 hours, respectively, to obtain carbon-coated SiO2 / C; Step (5) Preparation of SiOx / C composite material Take 6 g of carbon-coated SiO2 / C from step (4) and add it to 60 mL of deionized water, and stir for 3 h. Then add 7 mL of ammonia water (NH3H2O) and continue stirring for 3 h. Heat the solution to 60 ° C for 15 h. Collect the silicon submicron sphere precursor by centrifugation. Then put 7 g of the silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace. In an Ar (argon) atmosphere, heat it to 820 ° C at a rate of 6 ° C·min-1 and calcine it for 4 h. After cooling, SiOx / C composite materials; Step (6) Preparation of Si / SiOx / C Take 12g of SiO x The Si / SiOx / C composite material was added to 2 mol / L HCl (hydrogen chloride) to prepare a 2 M solution, and ultrasonicated at room temperature for 40 min. 6 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 15 min. 6 g of ammonium persulfate was weighed to prepare a 0.6 M ammonium persulfate solution. The solution was then magnetically stirred at room temperature for 13 h to obtain a dark green suspension, which was centrifuged at 9700 rpm, vacuum dried at 90 ° C for 15 h, and carbonized at 1500 ° C for 2.5 h in a tubular furnace under an Ar (argon) atmosphere to obtain Si / SiOx / C.

[0032] Example 3 Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 4:6 to generate a by-product of hydrogen chloride (HCl). The reaction product is separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber with an operating pressure range of 40Pa and an operating temperature range of 20°C. The top temperature of the washing tower is controlled at -28°C, the pressure is controlled at 1.1MPa, and the temperature difference is controlled at 3°C. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower, and after screening, electronic grade hydrochloric acid is obtained; Step (2) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions, and the product is chlorinated at high temperature (800°C) to obtain SiCl4 (silicon tetrachloride); Step (3) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor at a mass ratio of 3:3 g, react together at 14°C, heat to 37°C, and react for 3 hours to obtain tetraethyl orthosilicate (TEOS); Step (4) Preparation of carbon-coated SiO2 / C According to the volume ratio of 17:4:7, ethanol, deionized water and tetraethyl orthosilicate (TEOS) of step (3) are placed in a beaker in turn, and stirred for 3 hours. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 0.7 g / mL citric acid solution. Then, ethylene glycol is dropped into the citric acid solution according to a volume ratio of 3:60, and stirred at a constant temperature of 80°C. The mixture is dried in an electric oven at a drying temperature and time of 140°C and 7 hours, respectively. After the solid is taken out and ground into powder, it is pre-calcined in a tubular furnace. The pre-calcination atmosphere, temperature and time are air atmosphere and 500°C and 6 hours, respectively. After the pre-calcination is completed, xenon gas is introduced into the tubular furnace for calcination at a calcination temperature and time of 950°C and 7 hours, respectively, to obtain carbon-coated SiO2 / C; Step (5) Preparation of SiOx / C composite material Take 7g of carbon-coated SiO2 / C from step (4) and add it to 70mL of deionized water, and stir for 4h. Add 8mL of ammonia water (NH3H2O) and continue stirring for 4h. Heat the solution to 70℃ and react for 16h. Collect the silicon submicron sphere precursor by centrifugation. Then put 8g of silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace. In an Ar (argon) atmosphere, heat it to 890℃ at a rate of 7℃·min-1 and calcine it for 6h. After cooling, SiO x / C composite materials; Step (6) Preparation of Si / SiOx / C Take 17 g of SiO x The Si / SiOx / C composite material was added to 4 mol / L HCl (hydrogen chloride) to prepare a 4 M solution, and ultrasonicated at room temperature for 55 min. 7 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 17 min. 7 g of ammonium persulfate was weighed to prepare a 0.7 M ammonium persulfate solution, and then magnetic stirring was continued at room temperature for 18 h to obtain a dark green suspension, which was centrifuged at 9900 rpm, vacuum dried at 95 ° C for 18 h, and placed in a tubular furnace for carbonization at 1800 ° C for 4 h in an Ar (argon) atmosphere to obtain Si / SiOx / C.

[0033] Example 4 Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 5:7 to generate a by-product of hydrogen chloride (HCl), the reaction product is separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber, the operating pressure range is 60kPa, the operating temperature range is 80℃, the top temperature of the washing tower is controlled at -25℃, the pressure is controlled at 1.1MPa, and the temperature difference is controlled at 5℃. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower, and after screening, electronic grade hydrochloric acid is obtained; Step (2) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions and the product is chlorinated at high temperature (1100°C) to obtain SiCl4 (silicon tetrachloride); Step (3) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor at a mass ratio of 5:5 g, react together at 15°C, heat to 40°C, and react for 5 hours to obtain tetraethyl orthosilicate (TEOS); Step (4) Preparation of carbon-coated SiO2 / C According to the volume ratio of 20:5:10, ethanol, deionized water and tetraethyl orthosilicate (TEOS) of step (3) are placed in a beaker in turn, and stirred for 5 hours. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 0.9 g / mL citric acid solution. Then, ethylene glycol is dropped into the citric acid solution according to the volume ratio of 5:80, and stirred at a constant temperature of 100°C. The mixture is dried in an electric oven at a drying temperature and time of 150°C and 20 hours, respectively. After the solid is taken out and ground into powder, it is pre-calcined in a tubular furnace. The pre-calcination atmosphere, temperature and time are air atmosphere and 600°C and 10 hours, respectively. After the pre-calcination is completed, xenon gas is introduced into the tubular furnace for calcination at a calcination temperature and time of 1000°C and 10 hours, respectively, to obtain carbon-coated SiO2 / C; Step (5) Preparation of SiOx / C composite material Take 10g of carbon-coated SiO2 / C from step (4) and add it to 100mL of deionized water, and stir for 5h. Add 10mL of ammonia water (NH3H2O) and continue stirring for 5h. Heat the solution to 100℃ and react for 20h. Collect the silicon submicron sphere precursor by centrifugation. Then put 10g of the silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace. In an Ar (argon) atmosphere, heat it to 1000℃ at a rate of 10℃·min-1℃·min-1 and calcine it for 10h. After cooling, SiO x / C composite materials; Step (6) Preparation of Si / SiOx / C Take 20g of SiO x The Si / SiOx / C composite material was added to 5 mol / L HCl (hydrogen chloride) to prepare a 5 M solution, and ultrasonicated at room temperature for 60 min. 10 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 20 min. 10 g of ammonium persulfate was weighed to prepare a 1 M ammonium persulfate solution, and then magnetic stirring was continued at room temperature for 20 h to obtain a dark green suspension, which was centrifuged at 10000 rpm, vacuum dried at 100°C for 20 h, and carbonized at 2000°C for 5 h in a tubular furnace under an Ar (argon) atmosphere to obtain Si / SiOx / C.

[0034] Comparative Example 1 Step (1) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is soaked with electronic grade hydrochloric acid to remove the alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions and the product is chlorinated at high temperature (1300°C) to obtain SiCl4 (silicon tetrachloride). Step (2) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (1) into a reactor at a mass ratio of 6:8 g, react together at 20° C., heat to 60° C., and react for 8 h to obtain tetraethyl orthosilicate (TEOS); Step (3) Preparation of carbon-coated SiO2 / C According to the volume ratio of 26:6:13, ethanol, deionized water and tetraethyl orthosilicate (TEOS) of step (2) are placed in a beaker in turn, and stirred for 6 hours. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 1g / mL citric acid solution. Then, ethylene glycol is dropped into the citric acid solution according to a volume ratio of 7:90, and stirred at a constant temperature of 120°C. The mixture is dried in an electric oven at a drying temperature and time of 180°C and 24 hours, respectively. After the solid is taken out and ground into powder, it is pre-calcined in a tubular furnace. The pre-calcination atmosphere, temperature and time are air atmosphere, 700°C and 13 hours, respectively. After the pre-calcination is completed, xenon gas is introduced into the tubular furnace for calcination at a calcination temperature and time of 1100°C and 11 hours, respectively, to obtain carbon-coated SiO2 / C; Step (4) Preparation of SiOx / C composite material Take 12g of carbon-coated SiO2 / C from step (3) and add it to 110mL of deionized water and stir for 6h. Then add 11mL of ammonia water (NH3H2O) and continue stirring for 7h. Heat the solution to 120℃ and react for 23h. Collect the silicon submicron sphere precursor by centrifugation. Then put 14g of the silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace. In an Ar (argon) atmosphere, heat it to 1100℃ at a rate of 12℃·min-1 and calcine it for 12h. After cooling, SiO x / C composite materials; Step (5) Preparation of Si / SiOx / C Take 25g of SiO x The Si / SiOx / C composite material was added to 7 mol / L HCl (hydrogen chloride) to prepare an 8 M solution, and ultrasonicated at room temperature for 70 min. 12 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 22 min. 12 g of ammonium persulfate was weighed to prepare a 2 M ammonium persulfate solution, and then magnetic stirring was continued at room temperature for 25 h to obtain a dark green suspension, which was centrifuged at 11000 rpm, vacuum dried at 110°C for 30 h, and carbonized at 3000°C for 6 h in a tubular furnace under an Ar (argon) atmosphere to obtain Si / SiOx / C.

[0035] Comparative Example 2 Step (1) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid to remove the alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions and the product is chlorinated at high temperature (1700°C) to obtain SiCl4 (silicon tetrachloride). Step (2) Preparation of carbon-coated SiO2 / C According to the volume ratio of 30:7:15, ethanol, deionized water and SiCl4 (silicon tetrachloride) in step (1) are placed in a beaker in turn, and stirred for 7 hours. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 2g / mL citric acid solution. Then, ethylene glycol is dropped into the citric acid solution according to a volume ratio of 8:100, and stirred at a constant temperature of 130°C. The mixture is dried in an electric oven at a drying temperature and time of 190°C and 28 hours, respectively. After the solid is taken out and ground into powder, it is pre-calcined in a tubular furnace. The pre-calcination atmosphere, temperature and time are air atmosphere, 710°C and 15 hours, respectively. After the pre-calcination is completed, xenon gas is introduced into the tubular furnace for calcination at a calcination temperature and time of 1200°C and 12 hours, respectively, to obtain carbon-coated SiO2 / C; Step (3) Preparation of SiOx / C composite material Take 14g of carbon-coated SiO2 / C from step (2) and add it to 110mL of deionized water, and stir for 7h. Then add 13mL of ammonia water (NH3H2O) and continue stirring for 8h. Heat the solution to 170℃ and react for 24h. Collect the silicon submicron sphere precursor by centrifugation. Then put 16g of the silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace. In an Ar (argon) atmosphere, heat it to 1200℃ at a rate of 14℃·min-1 and calcine it for 13h. After cooling, SiO x / C composite materials; Step (4) Preparation of Si / SiOx / C Take 30g of SiO x The Si / SiOx / C composite material was added to 8 mol / L HCl (hydrogen chloride) to prepare a 9 M solution, and ultrasonicated at room temperature for 80 min. 15 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 25 min. 16 g of ammonium persulfate was weighed to prepare a 3 M ammonium persulfate solution. The solution was then magnetically stirred at room temperature for 30 h to obtain a dark green suspension, which was centrifuged at 12000 rpm, vacuum dried at 130 ° C for 40 h, and carbonized at 4000 ° C for 7 h in a tubular furnace under an Ar (argon) atmosphere to obtain Si / SiOx / C.

[0036] Comparison of detection experiments: The high energy storage negative electrode materials obtained in Examples 1 to 4 and the comparative products 1 and 2 were tested. The specific testing method is as follows: Electrochemical performance test method The prepared high energy storage negative electrode material was used as the negative electrode material of lithium-ion battery and the electrochemical cycle test was carried out. -1500 charge and discharge cycles at a current density of can reflect the Coulomb efficiency, which can indicate the reversible storage and release efficiency of charge in each charge and discharge cycle. If the percentage of Coulomb efficiency is higher, it indicates that the energy loss during the charge and discharge process is smaller, indicating that the battery will have higher performance. If the percentage of Coulomb efficiency is lower, then vice versa.

[0037] Electrochemical Impedance Spectroscopy (EIS) Electrochemical impedance spectroscopy (EIS) obtains frequency-dependent impedance data by applying a small-amplitude sinusoidal AC voltage across the two ends of an electrochemical cell and measuring the resulting current response. This test uses the prepared high-energy storage negative electrode material as the negative electrode material of the battery. The impedance value is generally 0-300Ω. If the test value is low, then the resistance is low, and the conductivity of the prepared negative electrode material is better. If the test value is high, then vice versa.

[0038] Constant current charge and discharge cycle method (CCCD) Constant current charge and discharge cycle (CCCD) refers to an activation cycle before the prepared negative electrode material is used for the first time. The battery capacity of the negative electrode material can be seen from the tested value. The discharge ratio capacity is generally 0-2000 (mA·h) / g. If the discharge ratio value is large, it indicates that the battery has a higher energy storage capacity, indicating that the available capacity is more. If the discharge ratio value is small, the opposite is true.

[0039] Figure 1 It is a negative electrode material with high energy storage and its application process in solid-state batteries.

[0040] Figure 2 The scanning electron microscope images of the Si / SiOx / C negative electrode materials prepared in the embodiment and the comparative example show that the Si / SiOx / C negative electrode materials prepared in the embodiment have more uniform particle size, more rounded shape, and more uniform dispersion than those in the comparative example.

[0041] Table 1 shows the coulomb efficiency test results. As can be seen from Table 1, Example 1 is the best and Comparative Example 2 is relatively poor. The coulomb efficiency of Example 1 is 85%, indicating that in the charge and discharge cycle of Example 1, the reversible storage and release efficiency of charge is very high, the energy loss is very small, and the battery has a higher performance. In Comparative Example 2, the coulomb efficiency is 74%, indicating that there is a large amount of energy loss during the charge and discharge process, and the storage and release efficiency of charge is low.

[0042] Table 1 Electrochemical performance test method

[0043] Table 2 shows the results of electrochemical impedance test. As can be seen from Table 2, Example 1 is the best and Comparative Example 2 is worse. In Example 1, the impedance value is 28Ω, indicating that the charge transfer between the electrode material and the electrolyte of the prepared negative electrode material is faster, which improves the power density of the battery, indicating that its charge transfer ability is stronger, the conductivity is better, and the energy efficiency is higher. The impedance value of Comparative Example 2 is 58Ω, indicating that its charge transfer process is subject to greater resistance, the conductivity is poor, and the energy efficiency is low.

[0044] Table 2 Electrochemical impedance spectroscopy (EIS)

[0045] Table 3, Table 4 and Figure 2 , Figure 3 The results of electrochemical charge and discharge tests. It can be seen from Tables 3 and 4 that Example 1 is the best and the comparative example is worse. In Example 1, its discharge capacity is 1751.87 (mA·h) / g, and the capacity retention rate after 100 cycles is 98.34%, indicating that the negative electrode material prepared in Example 1 has a higher energy density, more available capacity, and better cycle performance of the negative electrode material. The discharge capacity of Comparative Example 2 is 1578.73 (mA·h) / g, and the capacity retention rate after 100 cycles is 90.53%, which is worse than that of the embodiment. The charge and discharge curves are shown in Figure 2. Figure 2 Cyclic performance test Figure 3 shown.

[0046] Table 3 Constant current charge and discharge cycle method (CCCD)

[0047] Table 4 Cycle capacity retention rate

[0048] This specific embodiment is merely an explanation of the present invention, and it is not a limitation of the present invention. A person skilled in the art can make non-creative modifications to the present embodiment as needed after reading this specification. However, as long as it is within the scope of the claims of the present invention, it is protected by the patent law.

Claims

1. A negative electrode material with high energy storage and its application in a solid-state battery, characterized in that: include: Preparation of electronic grade hydrochloric acid, preparation of SiCl4 (silicon tetrachloride), preparation of tetraethyl orthosilicate (TEOS), preparation of carbon-coated SiO2 / C, preparation of SiO x Preparation of / C composite materials, preparation of Si / SiOx / C.

2. The negative electrode material with high energy storage and its application in solid-state batteries according to claim 1, characterized in that: Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a certain ratio to generate a by-product of hydrogen chloride (HCl). The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber. The top temperature of the washing tower is controlled below zero. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic grade hydrochloric acid is obtained; Step (2) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions and the product is chlorinated at high temperature to obtain SiCl4 (silicon tetrachloride); Step (3) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor in a certain mass ratio, react together, raise the temperature together, and react for a period of time to obtain tetraethyl orthosilicate (TEOS); Step (4) Preparation of carbon-coated SiO2 / C According to a certain ratio, ethanol, deionized water and tetraethyl orthosilicate (TEOS) in step (3) are sequentially placed in a beaker, stirred, and after sufficient stirring, a mixed solution is obtained, the mixed solution is poured into a citric acid solution, and then ethylene glycol is dripped into the citric acid solution according to a certain volume ratio, stirred at a constant temperature, dried in an electric oven, and the solid is taken out and ground into powder, and then pre-fired in a tubular furnace. After the pre-fired treatment is completed, xenon gas is introduced into a tubular furnace for calcination to obtain carbon-coated SiO2 / C; Step (5) Preparation of SiOx / C composite material A small amount of the carbon-coated SiO2 / C prepared in step (4) is added to deionized water, stirred, and ammonia (NH3H2O) is added and stirred continuously. The solution is heated and reacted for a period of time. The silicon submicron sphere precursor is collected by centrifugation. The silicon submicron sphere precursor is then placed in a corundum crucible and placed in a tube furnace. The temperature is raised at a certain rate and calcined in an Ar (argon) atmosphere. After cooling, SiO2 / C is obtained. x / C composite materials; Step (6) Preparation of Si / SiOx / C Take a small amount of SiO x The Si / SiOx / C composite material is added into HCl (hydrogen chloride) to form a solution, ultrasonicated at room temperature for a period of time, added with a small amount of aniline (C6H7N), transferred to a magnetic stirring at room temperature, ammonium persulfate is weighed, an ammonium persulfate solution is prepared, and then magnetic stirring at room temperature is continued to obtain a dark green suspension, which is centrifuged, vacuum dried, and placed in a tubular furnace for carbonization under an Ar (argon) atmosphere for a period of time to obtain Si / SiOx / C.

3. The negative electrode material with high energy storage and its application in solid-state batteries according to claim 2, characterized in that: Step (1) Preparation of electronic grade hydrochloric acid With trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 1-5:2-7 to generate a by-product of hydrogen chloride (HCl). The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and loaded into a washing tower. The washing tower adopts a round hole block graphite falling film absorber with an operating pressure range of 0-60 kPa and an operating temperature range of -25-80°C. The top temperature of the washing tower is controlled at -35--25°C, the pressure is controlled at 0.9-1.1 MPa, and the temperature difference is controlled at 0-5°C. In the washing tower, the hydrogen chloride gas contacts and absorbs the low-concentration hydrochloric acid from the bottom of the tail gas tower, and after screening, electronic grade hydrochloric acid is obtained.

4. The negative electrode material with high energy storage and its application in solid-state batteries according to claim 3, characterized in that: Step (2) Preparation of SiCl4 (silicon tetrachloride) First, the rice husk is washed with electronic grade hydrochloric acid in step (1) to remove the alkaline substances and soluble metal ions contained therein, and then the rice husk is carbonized under anaerobic conditions and the product is chlorinated at high temperature (600-1100°C) to obtain SiCl4 (silicon tetrachloride).

5. The negative electrode material with high energy storage and its application in solid-state batteries according to claim 4, characterized in that: Step (3) Preparation of tetraethyl orthosilicate (TEOS) Add SiCl4 (silicon tetrachloride) and anhydrous C2H5OH (anhydrous ethanol) in step (2) into the reactor in a mass ratio of 1-5:1-5 g, react together at 10-15° C., heat to 30-40° C., and react for 2-5 hours to obtain tetraethyl orthosilicate (TEOS).

6. The negative electrode material with high energy storage and its application in solid-state batteries according to claim 5, characterized in that: Step (4) Preparation of carbon-coated SiO2 / C In a beaker, ethanol, deionized water and tetraethyl orthosilicate (TEOS) in step (3) are placed in a ratio of 13-20:1-5:2-10 by volume, and stirred for 1-5 hours. After sufficient stirring, a mixed solution is obtained, and the mixed solution is poured into a 0.3-0.9 g / mL citric acid solution. Then, ethylene glycol is dripped into the citric acid solution in a ratio of 1-5:40-80 by volume, and stirred at a constant temperature of 60-100 °C. 0℃, dried in an electric oven, the drying temperature and time are 120-150℃ and 12-20h respectively, take out the solid and grind it into powder, and pre-sinter it in a tubular furnace. The pre-sintering atmosphere, temperature and time are air atmosphere and 350-600℃ and 4-10h respectively. After the pre-sintering, xenon gas is introduced into the tubular furnace for calcination, the calcination temperature and time are 900-1000℃ and 4-10h respectively, to obtain carbon-coated SiO2 / C.

7. The negative electrode material with high energy storage and its application in solid-state batteries according to claim 6, characterized in that: Step (5) Preparation of SiOx / C composite material Take 5-10 g of carbon-coated SiO2 / C from step (4) and add it to 50-100 mL of deionized water and stir for 2-5 h. Add 5-10 mL of ammonia (NH3H2O) and continue stirring for 1-5 h. Heat the solution to 50-100 °C and react for 12-20 h. Collect the silicon submicron sphere precursor by centrifugation. Then put 5-10 g of the silicon submicron sphere precursor into a corundum crucible and place it in a tube furnace. In an Ar (argon) atmosphere, heat it at 5-10 °C·min -1 The temperature was raised to 800-1000℃ and calcined for 3-10h. SiO x / C composite material.

8. The negative electrode material with high energy storage and its application in solid-state batteries according to claim 7, characterized in that: Step (6) Preparation of Si / SiOx / C Take 10-20 g of SiO x The Si / SiOx / C composite material was added to 1~5 mol / L HCl (hydrogen chloride) to prepare a 1~5 M solution, and ultrasonicated at room temperature for 30~60 min. 5~10 g of aniline (C6H7N) was added, and the solution was transferred to a magnetic stirring chamber at room temperature for 10~20 min. 5~10 g of ammonium persulfate was weighed to prepare a 0.5~1 M ammonium persulfate solution. The solution was then magnetically stirred at room temperature for 12~20 h to obtain a dark green suspension. The suspension was centrifuged at 9600~10000 rpm, vacuum dried at 80~100°C for 12~20 h, and carbonized at 1000~2000°C for 2~5 h in a tubular furnace under an Ar (argon) atmosphere to obtain Si / SiOx / C.